2013
DOI: 10.1111/jace.12189
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Synthesis of Needle‐like α‐FeOOH and Their Conversion into α‐Fe2O3 Nanorods for Humidity Sensing Application

Abstract: In this study, we report template and surfactant‐free, low temperature (70°C) synthesis of needle‐like α‐FeOOH and its conversion at 400°C into α‐Fe2O3 nanorods using Fe(+2) and Fe(+3) chlorides and urea as a hydrolysis‐controlling agent. The isolated needle‐like α‐FeOOH indicates asparagus‐type growth pattern having length ca. 600 nm with 80 nm diameter at base and apex diameter of around 10 nm. The sample on heating (α‐Fe2O3) shows nanorod‐like morphology. The samples were characterized using various physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…As is well-known, α-FeOOH can be converted to α-Fe 2 O 3 at high temperature [4,6,20]. In order to confirm the phase transition temperature, Fig.7 gives the TG-DTA curves of acicular α-FeOOH powder hydrothermally synthesized with 0.2 g CTAB at 180ºC.…”
Section: Conversion To Rice-like α α α α-Fe 2 O 3 After Annealingmentioning
confidence: 92%
“…As is well-known, α-FeOOH can be converted to α-Fe 2 O 3 at high temperature [4,6,20]. In order to confirm the phase transition temperature, Fig.7 gives the TG-DTA curves of acicular α-FeOOH powder hydrothermally synthesized with 0.2 g CTAB at 180ºC.…”
Section: Conversion To Rice-like α α α α-Fe 2 O 3 After Annealingmentioning
confidence: 92%
“…In Figure (a), two strip broad absorption band of α-FeOOH nanorods mainly located in an area away from UV. One of these bands located at wavelengths of 280-300 nm and the other of 360-380 nm which is similar to the absorption band of α-FeOOH nanoneedles [72]. There was no specific absorption in the visible regime but according to Sherman and colleagues [73] we can say that the intensity of α-Fe 2 O 3 nanorods is greater than α-FeOOH nanorods.…”
Section: Photocatalytic Applications Of Magnetic Iron Nanorodsmentioning
confidence: 70%
“…It results in the coalescence of adjacent small particles into a larger one. 34 The optical absorption properties of the a-Fe 2 O 3 nanostrings and nanoropes were investigated to study the effect of size on their band structures as shown in Fig. When the temperature reaches 600 C, the size of these particles is large enough that equals the ber diameter, resulting in the appearance of the string-of-bead morphology.…”
Section: Structural and Morphological Characteristicsmentioning
confidence: 99%